Review of low-cost sensors for indoor air quality: Features and applications. Issue 9 (20th October 2022) - Ródenas García, Milagros; Spinazzé, Andrea; Branco, Pedro T.B.S.; Borghi, Francesca; Villena, Guillermo; Cattaneo, Andrea; Di Gilio, Alessia; Mihucz, Victor G.; Gómez Álvarez, Elena; Lopes, Sérgio Ivan; Bergmans, Benjamin; Orłowski, Cezary; et al.
Abstract: Humans spend the majority of their time indoors, where they are potentially exposed to hazardous pollutants. Within this context, over the past few years, there has been an upsurge of low-cost sensors (LCS) for the measurement of indoor air pollutants, motivated both by recent technological advances and by increased awareness of indoor air quality (IAQ) and its potential negative health impacts. Although not meeting the performance requirements for reference regulatory-equivalent monitoring indoors, LCS can provide informative measurements, offering an opportunity for high-resolution monitoring, emission source identification, exposure mitigation and managing IAQ and energy efficiency, among others. This article discusses the strengths and limitations that LCS offer for applications in the field of IAQ monitoring; it provides an overview of existing sensor technologies and gives recommendations for different indoor applications, considering their performance in the complex indoor environment and discussing future trends.